Analisis Pengetahuan Penggunaan Obat-Obatan Analgesik pada Mahasiswa Poltekkes Kemenkes Pangkalpinang - Pratiwi, Rahma; Liannuari, Delvy; Yasoli, Putri; Salsabila, Rania; Maharani, Lieyoni Aprilia (Lembaga Intelektual Muda (LIM) Maluku, 2025)
The harmful impact of medication misuse can cause side effects that may become increasingly severe over time. One of the drugs commonly used in self-medication practices is analgesic drugs. Analgesic drugs, if used in excessive doses, can produce several side effects. This study was conducted to analyze the knowledge of analgesic drug use among students of Poltekkes Kemenkes Pangkalpinang. This research is a descriptive qualitative study with a cross-sectional approach, using direct interview methods and a total purposive sampling technique based on inclusion and exclusion criteria. Data analysis was carried out qualitatively through data reduction, data presentation, and drawing conclusions. The analysis results show that the majority of students use analgesics only when experiencing pain and do not finish the medication, indicating an understanding of use as needed. However, there are still gaps in knowledge related to usage rules, particularly regarding dosage and frequency, as well as a low understanding of side effects such as stomach and kidney problems. The main sources of information for students about analgesics come from healthcare professionals, although some also obtain information from friends, family, and social media. Students already have a good basic knowledge of the definition and function of analgesics, but they still need further education on the correct usage rules and potential side effects to ensure safer and more rational use of analgesics.